Self-administration of vitamin D supplements in the general public may be associated with high 25-hydroxyvitamin D concentrations. (May 2017) - Shea, Robyn L; Berg, Jonathan D
Introduction: Our dried blood spot vitamin D testing service enables members of the public to assess their vitamin D status. Vitamin D has become popular with the media and the general public. We noticed that our direct access service had a higher rate of high to toxic 25-hydroxyvitamin D levels compared with our GP population and we wanted to know why. Methods: Between January 2013 and September 2015 we contacted all direct access users who had 25-hydroxyvitamin D >220 nmol/L measured using LC/MS/MS. We investigated the amount, type and length of supplementation used and whether or not users were medically supervised. Results: A total of 372 service users had 25-hydroxyvitamin D concentrations >220 nmol/L. Of 14, 806 direct access samples received, 372 (2.5%) were from users with 25-hydroxyvitamin D concentrations ranging from 221 to 1235 nmol/L. Only 0.06% of GP patients had results >220 nmol/L over the same time frame. There were 361 direct access users regularly supplementing, taking between 1000 to 120, 000 IU/day. Two users took bolus doses of 300, 000 and 900, 000 IU. Only 23 users taking supplements (6.4%) were under medical supervision. There were 28 users with levels >500 nmol/L, but only one was under medical supervision. The internet was the main source of supplements (74%). Conclusions: The proportion of high to toxic concentrations of vitamin D was higher in direct access users than in the GP population. Many people were taking more than the Institute of Medicine's recommendation of 10, 000 IU/day, yet only a few were being medically supervised. Clinicians should be aware that patients may be self-administering very high concentrations of vitamin D, especially when investigating unexplained hypercalcaemia.